Planning field trips as a teaching and learning strategy in legal education: some points for consideration / Nor Fadzlina Nawi and Amylia Fuziana Azmi - Nawi, Nor Fadzlina; Azmi, Amylia Fuziana (Penerbit UiTM (UiTM Press), 2018)
Field trips can be a valuable tool in making learning more engaging and provide unique opportunities for learning certain concepts, including legal concepts by putting them into a more realistic and relevant context. Research studies have shown that there is a significant increase in participants’ factual knowledge and conceptual understanding after participation in a well-designed field trip. However, due to differences in academic disciplines, elements which constitute a well-designed field trip vary according to the learning objectives of the field trip. Thus far, in legal education, there has been a dearth of both theoretical and empirical research into the elements necessary in the planning of field trips as a successful pedagogic tool. Therefore, in this article, the authors seek to analyse the important elements that should be emphasized in designing a successful field trip for legal educators. Drawing upon literature from other disciplines, the article concentrates its review on Myers and Jones’ field trip planning model in the determination of the elements that should be present in a well-designed field trip. Some thoughts and considerations in the application of the model into planning field trips for legal education are also discussed and recommendations are made appropriately in adapting the model.